Pemanfaatan Biomassa Serbuk Gergaji Sebagai Penyerap Logam Timbal - Intan, Dey; Said, Irwan; Abram, Paulus Hengky (Jurnal Akademika Kimia, 2016)
Lead (Pb) is one kind of heavy metal that has high level of toxicity. One way to reduce the level of Pb is by adsorption using cellulose and lignin of sawdust. The aim of this study is to determine the optimum pH, the optimum weight and to determine the adsorption capacity of sawdust when it absorbs Pb in solution of Pb(NO3)2. The adsorption process is carried out by using the various pH of 3, 4, 5, 6, 7, and 8 with a weight of 100 mg, and then the various weight of 100, 200, 300, 400, and 500 mg with the pH optimum. The analysis of Pb content in the solution was conducted by Spectro-direct. The analysis result shows the determination of pH occured at pH 7, Pb absorbed is 14.89 mg/g, and the percentage of Pb absorbed was 96.97%. For the determination of 400 mg of the adsorbent weight of Pb absorbed was 3,83 mg/g, the adsorption percentage of Pb was 99.98%, and the optimum adsorption for optimum weight was 0.15 mg Pb/mg sawdust.